Gradient-Based Optical Flow for Large Motion Using Multi-Resolution Smoothing Operation Pre-Processing Technique - Hossain Sarker, Md. Mosharrof; Bechkoum, Kamal (Malaysian Journal of Computer Science, 2006)
Motion estimation is a key problem in the analysis of image sequences. From image sequences, we can only estimate an approximation of the image motion called optical flow. In this paper, we present the gradient-based optical flow method that estimates the two-dimensional velocity of object motion. A multi-resolution smoothing operation proposes in this paper as a preprocessing step for overcoming the difficulty of large motion estimation by gradient-based optical flow techniques. The effectiveness of the proposed method has confirmed by applying image sequence of large motion. Experimental results with an image sequence show a qualitative improvement.